Accountant profession and ethics of its behavior - Haman, H.; Zinchenko, M . (Ways to Improve Construction Efficiency, 2022)
The article reveals important aspects of the profession of an accountant, the ethical norms of accountant´s behaviour, and the social and moral norms of behavior for individuals in this professional group. The main objectives of business ethics are highlighted, including key components of the professional accounting ethics, which were originally developed in the United States in the form of an ethical code for accountants. The essence of professional ethics for accountants and auditors is defined as a code of relevant rules that determine the behavior of specialists in the workplace, as well as norms that correspond to existing legislative and regulatory acts and official regulatory documents, professional knowledge, relationships in the team, a deep awareness of moral responsibility for performance professional duties. An important place in professional ethics belongs to consideration of the professional responsibility of a specialist in the field of accounting and auditing. The authors note that it is relevant for the domestic market to adhere to foreign practices, where violations of professional ethics, including the code of ethics for professional accountants and auditors, can lead to the revocation of a license to practice within the profession after review by special committees. The priority role in the education of highly qualified specialists and their compliance with ethical rules belongs to the sphere of education, particularly higher educational institutions, advanced training courses, webinars, conferences, etc. Science, education, and practical experience of specialists should create the basis for professional knowledge, skills, values, ethics, and attitudes toward the profession. The article describes the profession of an accountant as one of the most responsible professions, as errors in financial documents can result in significant fines for business owners. Competencies and personal characteristics of accountants in modern conditions and the realities of our lives are also mentioned.